Physiological and Perceptual Responses to Single-player vs. Multiplayer Exergaming - Soria Campo, Aarón; Wang, Alf Inge; Moholdt, Trine; Berg, Jonathan (Frontiers in Sports and Active Living, 2022)
Rationale Since many modern exergames include a multiplayer component, this study aimed to compare the physiological and perceptual responses between playing a cycling exergame alone or with others. Methods In this randomized crossover study, 15 healthy individuals aged between 10 and 30 years completed a single-player and a multiplayer exergaming session. The main outcomes were exercise intensity, measured as oxygen uptake (V°O2) and heart rate (HR), and perceived enjoyment, pleasure, and exertion. Results Peak HR was significantly higher during multiplayer (172 ± 23 beats per minute [bpm]) vs. single-player exergaming (159 ± 27 bpm) with a mean difference of 13 bpm (95% CI: 2 to 24, p = 0.02). Peak V°O2 was 33.6 ± 9.5 mL·kg−1·min−1 and 30.4 ± 9.1 mL·kg−1·min−1 during multiplayer and single-player exergaming, respectively with no statistically significant difference between conditions (3.2, 95% CI: −0.2–6.6 mL·kg−1·min−1, p = 0.06). Average HR, average V°O2 and perceptual responses did not differ between single- and multiplayer exergaming. Conclusion Other than inducing a higher HR, multiplayer exergaming showed no significant benefits on exercise intensity or perceptual responses over single-player exergaming. However, the higher peak HR and a tendency of higher peak V°O2 intensity during multiplayer exergaming imply that multiplayer exergaming may offer some advantages over single-player exergaming that could impact the potential health benefits of exergaming.